Molecular taxonomic report of Nitella megacephala sp. nov. (Characeae, Charophyceae) from Korea - Lee, Eun-Young; Bae, Eun Hee; Choi, Kwang Chul; Kim, Jee-Hwan; Lee, Sang-Rae (Phytotaxa, 2019)
We report a new taxonomic entity of Nitella megacephala sp. nov. (Charales, Charophyceae) from Korea. The characean algae collected from two sites (Haenam-gun and Kangjin-gun) had distinctive morphological characteristics representing a new Nitella species. Those samples showed a light-green color in gross morphology and a plant body length up to 13 cm. Moreover, the two-celled dactyls and head formation differed clearly from closely related Nitella species (N. moriokae, N. spiciformis, and N. translucens). From a molecular phylogenetic analysis of rbcL DNA sequences, Nitella megacephala sp. nov formed a single clade with N. translucens, N. moriokae and N. spiciformis, and was distantly related to those three species as a sister taxon. In the terms of interspecific sequence variation, Nitella megacephala showed 3.2–5.5% pairwise distance values with sister groups in phylogenetic tree (N. translucens, N. moriokae and N. spiciformis) and 3.2–9.1% with other of Nitella species. In contrast, its sister group species differed 0.3–1.7% at the interspecific level. These unique morphological and molecular taxonomic characteristics clearly support the establishment of this taxonomic entity as a new species in the genus Nitella (Nitella megacephala sp. nov.)